Rethinking the Proportional Design Principles of Timber-Framed Buddhist Buildings in the Goryeo Era - Ju-Hwan Cha (MDPI AG, 2021)
This study examines how the wooden architecture of the Goryeo Dynasty in Korea evolved in an original way while incorporating Chinese architectural principles. For the Goryeo Era’s timber-framed buildings, eave purlin height was determined according to √2H times the eave column height (H), while the eave column height influenced the proportional location of each purlin, determined by the √2H times decrease rate in the cross-section. Thus, eave column height was proportionately connected to a geometric sequence with a common ratio of √2H. This technical approach, achieved using an L-square ruler and a drawing compass, contributed to determining eave purlin and ridge post placement, bracket system height, and outermost bay width. This study notes that the practical works were consistently preserved in East Asian Buddhist architecture, in that a universal rule of proportion was applied to buildings constructed during the Tang–Song and the Goryeo Dynasties, surmounting differences in local construction methods. These design principles were a vestige of socio-cultural exchange on the East Asian continent and a minimal step toward the establishment of structurally safe framed buildings.